What hinders adoption of the electric bus in Canadian transit? Perspectives of transit providers. (October 2018) - Mohamed, Moataz; Ferguson, Mark; Kanaroglou, Pavlos
Highlights: We investigate factors that hinder the decision-making for adopting electric buses. A grounded theory analysis is applied to investigate the adoption of e-Bus. Transit providers have sound concerns on the adoption of electric buses in transit. The analysis of 11 interviews yielded factors governing the adoption of e-Bus. A detailed framework for a feasible path towards adopting electric bus is developed. Abstract: There is increasing advocacy for the electrification of mobility choices to reduce transport related GHG emissions. Bus transit has been always considered a promising context for electric powertrain technologies. Current market shares, however, tell a different story with a very small share for electric powertrains. This study identifies factors that hinder the implementation of the electric bus in the public transit context as seen from the perspective of service providers. A grounded theory analysis of 11 in-depth interviews yielded 55 themes/concerns, allocated over four categories, that appear to govern the adoption of the electric bus in Canadian transit. Risk mitigation, operational capabilities, and cost reductions are identified as significantly influencing the perspective of service providers and consequently the potential of the electric bus to penetrate the marketplace. The findings also highlighted that: political support, Canadian-based operational data, standardization, and demonstration projects are essential components that would move transit providers towards electric powertrains. Overall, the study provides a detailed blueprint for a feasible path towards implementation of the electric bus technologies in the urban transit context.